2019
DOI: 10.1177/2515841419827268
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the clinical estimation of cup-to-disk ratio by direct ophthalmoscopy and optical coherence tomography

Abstract: Objective: To compare the clinical estimation of cup-to-disk ratio determined by direct ophthalmoscopy and optical coherence tomography in glaucoma diagnosis and monitoring. Methods: A retrospective, cross-sectional study involving a review of 71 optical coherence tomography scans dating from June 2011 to January 2012 at a private imaging lab in Ghana. At the respective referring facilities, only 31 out of the 71 corresponding patient records were successfully reviewed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…However, W-OCT is considered more sensitive because it detects inflammation that is not apparent under ophthalmoscopy. OCT is more accurate than ophthalmoscopy for measurement because an objective assessment can be provided [15]. The present study showed that W-OCT may be more sensitive to inflammation than ophthalmoscopy.…”
Section: Discussionmentioning
confidence: 56%
“…However, W-OCT is considered more sensitive because it detects inflammation that is not apparent under ophthalmoscopy. OCT is more accurate than ophthalmoscopy for measurement because an objective assessment can be provided [15]. The present study showed that W-OCT may be more sensitive to inflammation than ophthalmoscopy.…”
Section: Discussionmentioning
confidence: 56%
“…The higher the PSNR value, the higher the level of audio signal than level of noise [25]. So, it is proven that the image quality after pre-processing is better than original image as noise was removed [26]. Table 2 indicates the PSNR value of original image before and after pre-processing was made.…”
Section: Results and Analysismentioning
confidence: 99%